İdeal Güzellik Algısı ve Matthias Verginer’in Heykellerindeki Kadın Figürlerde Güzellik Olgusu - Yildiz İlden, Serap; Bostanci, Emine (Atatürk Üniversitesi, 2022)
For centuries, the body has been an important factor in determining the social position and roles of women and men. However, it becomes possible to talk about a distinction between men and women in the sense dedicated to the body. The phenomenon of “beauty” takes its place at the beginning of the mentioned distinctions. “Beauty” has been one of the basic criteria preferred to define women in many cultures. However, the meaning of the phenomenon of beauty has changed depending on time and society. The perception of ideal beauty is a phenomenon that has undergone changes in the historical process. In addition, it differs from society to society, according to the development processes of societies and cultural structures. The perception of ideal beauty in humans has turned into a system of values that are largely addressed through women. For this reason, women were evaluated according to these "ideal beauty" criteria, and even those who did not comply with these criteria from time to time were excluded by being called ugly or other adjectives. Matthias Verginer, who puts overweight female figures in the center of his sculptures, ironically dealt with the perception of ideal beauty, and the female figures in his sculptures worked as overweight women. As a reaction to the objectification of the female body, the overweight female figures he made in his sculptures form the basis of this work.

Yüzyıllar boyu kadının ve erkeğin toplumsal konumunun ve rollerinin belirlenmesinde beden önemli bir faktör olmuştur. Bununla beraber bedene ithaf edilmiş olan anlamda erkek ve kadın arasında bir ayrımdan söz etmek mümkün hale gelmektedir. “Güzellik” olgusu, bahsi geçen ayrımların başında yerini almaktadır. “Güzellik”, birçok kültürde kadını tanımlamak adına tercih edilen temel ölçütlerden biri olmuştur. Fakat zamana ve topluma bağlı olarak güzellik olgusunun anlamı değişim göstermiştir. İdeal güzellik algısını tarihsel süreç içerisinde değişime uğrayan bir olgudur. Bunun yanı sıra toplumdan topluma, toplumların gelişim süreçlerine, kültür yapılarına göre de farklılıklar göstermektedir. İnsandaki ideal güzellik algısı ise büyük ölçüde kadın üzerinden ele alınan bir değerler sistemine dönüşmüştür. Bu nedenle kadınlar bu “ideal güzellik” ölçülerine göre değerlendirilmiş, hatta zaman zaman bu ölçülere uymayanlar çirkin ya da diğer sıfatlarla adlandırılarak dışlanmıştır. Kilolu kadın figürlerini heykellerinde merkezi konuma alan Matthias Verginer’ın, ideal güzellik algısını ironik bir şekilde ele almış ve heykellerindeki kadın figürleri kilolu kadınlar olarak çalışmıştır. Kadın bedeninin nesneleştirilmesine bir tepki olarak, heykellerinde yaptığı kilolu kadın figürleri bu çalışmanın temelini oluşturmaktadır.
Keywords: Matthias Verginer; Sculpture; Woman; Beau Ideal; Contemporary Art; Matthias Verginer; Heykel; Kadın; İdeal Güzellik; Çağdaş Sanat